Pembudayaan Permainan Tradisional sebagai Wahana Belajar Luar Ruang bagi Anak - Didik Hariyanto; Muhammad Abror; Muhammad Yani; Ferry Adhi Dharma (Universitas Muhammadiyah Yogyakarta, 2021)
The Covid-19 pandemic has made children even more interested in playing gadgets. The purpose of this community service activity is to reduce and change the dependence of early childhood on modern games, especially games on gadgets or smartphones. The method used was Participatory Rural Appraisal (PRA) by involving the Bait Kata community to design the concept of a literacy village, Karang Taruna to help socialize activities, and Dasa Wisma group to design UMKM and tourism awareness groups in Tebel Village, Gedangan District, Sidoarjo Regency. This community service activity develops the concept of learning and playing traditional games in one place that is integrated between playing, learning and becoming a center for educational tourism for children. The expected output targets include making the literacy village a center for children's educational tourism in Sidoarjo and improving the welfare of the surrounding community through educational tours. The result achieved in this program is the establishment of a reading terrace where children learn various knowledge from textbook and novel sources to foster children's interest in reading and writing, as well as traditional games such as stilts, clogs, and congklak (a playing board with two parallel rows of circular depression) that train interaction, cooperation, empathy, and children’abilities at mathematics. For the surrounding community, this service has helped empower the community's economy through UMKM in the field of traditional games and food called Kampung Literasi culinary corner. Teras Baca and UMKM center have been integrated and are ready to become an educational tourism destination of Kampung Literasi Tebel Barat.